Acinetobacter baumanniiphenylacetic acid metabolism influences infection outcome through a direct effect on neutrophil chemotaxis - Bhuiyan, Md Saruar; Ellett, Felix; Murray, Gerald L.; Kostoulias, Xenia; Cerqueira, Gustavo M.; Schulze, Keith E.; Mahamad Maifiah, Mohd Hafidz; Li, Jian; Creek, Darren J.; Lieschke, Graham J.; Peleg, Anton Y. (National Academy of Sciences, 2016)
Innate cellular immune responses are a critical first-line defense against invading bacterial pathogens. Leukocyte migration from the bloodstream to a site of infection is mediated by chemotactic factors that are often host-derived. More recently, there has been a greater appreciation of the importance of bacterial factors driving neutrophil movement during infection. Here, we describe the development of a zebrafish infection model to study Acinetobacter baumannii pathogenesis. By using isogenic A. baumannii mutants lacking expression of virulence effector proteins, we demonstrated that bacterial drivers of disease severity are conserved between zebrafish and mammals. By using transgenic zebrafish with fluorescent phagocytes, we showed that a mutation of an established A. baumannii global virulence regulator led to marked changes in neutrophil behavior involving rapid neutrophil influx to a localized site of infection, followed by prolonged neutrophil dwelling. This neutrophilic response augmented bacterial clearance and was secondary to an impaired A. baumannii phenylacetic acid catabolism pathway, which led to accumulation of phenylacetate. Purified phenylacetate was confirmed to be a neutrophil chemoattractant. These data identify a previously unknown mechanism of bacterial-guided neutrophil chemotaxis in vivo, providing insight into the role of bacterial metabolism in host innate immune evasion. Furthermore, the work provides a potentially new therapeutic paradigm of targeting a bacterial metabolic pathway to augment host innate immune responses and attenuate disease